Diagnostic features of pediatric testicular yolk sac tumors: a 13-year retrospective analysis - Xiaoli Zheng; Siqi Zhang; Taiya Chen; Huan Zhang; Shoulin Li; Hongwu Zeng; Wenhong Ye (World Journal of Surgical Oncology)
Abstract Background Testicular yolk sac tumor (YST) is a rare neoplasm with limited practical guidance for preoperative diagnostic assessment. This study aims to conduct a retrospective analysis of the value of clinical profiles and MRI parameters in accurately diagnosing pediatric testicular YST while exploring characteristic indicators for these patients. Methods This retrospective study analyzed eighty patients with a testicular mass who underwent surgical treatment and preoperative MRI. Clinical characters (age, preoperative serum alpha-fetoprotein (AFP) levels), and radiology features were recorded and compared. Subsequently, patients were categorized into YST and non-YST groups based on histology. Comparative statistical analyses were then used to compare factors between the two groups. The receiver operating characteristic curve (ROC) analysis was conducted to evaluate the diagnostic performance of the indicators for pediatric testicular YST. Results Forty patients (50%) were diagnosed with YST. In comparison to the non-YST group, patients with testicular YST were younger and had larger tumor sizes, accompanied by significantly elevated AFP levels. On MRI, most YST cases (n = 38) exhibited predominantly solid lesions, whereas non-YST tumors were more likely to contain cystic components. The bright dot sign and thickened spermatic cord might also be helpful in differentiating YST (p < 0.05). The optimal factor for diagnosing testicular YST was signal intensity, with an AUC value of 0.936 (95%CI: 0.877 ~ 0.995). Conclusions A predominantly solid testicular mass with a bright dot sign, thickened spermatic cord ipsilaterally, and elevated AFP levels should raise suspicion for YST.